(untitled) (Journal of Medical & Health Sciences Review, 2025)
The research aimed to observe the diurnal activity patterns of A. axis and A. porcinus during various seasons. Over a period from August, 2023 to June,2024,the study was conducted on two of herds of deer, A. porcinus and A. axis consisting of total of 12 individuals, each group consisting of six individuals with herd of A. porcinus having four males and two females and herd of A. axis having two males and four females. These two herds were observed. The diurnal activities of selected species were tracked for over four hours with thirty minutes intervals for three consecutive days at the wildlife park Fatehpur, Layyah, Punjab, Pakistan. The activities were observed from 6 am to 10 am on the first day, similarly from 10 am to 2 pm on the second day and from 2 pm to 6 pm on the third day. The same pattern was followed in order to observe selected species for nine days in each season from 6 am to 6 pm and activities of selected species were observed. The activities observed, including, feeding, resting, sleeping, ruminating, sitting, running, foraging, walking, standing, and various others, were documented using the naked eye, binoculars, and a camera (Canon 1200D DSLR). Results indicated that bucks and does A. porcinus considerably involved in foraging and walking during fall, while foraging activity was more seen during autumn. In winter standing and sitting enhanced while during spring they spent more time feeding, foraging and walking. During summer, activities were centered around sitting, sleeping and resting. Furthermore, doe A. porcinus exhibited increased durations of sitting, standing, feeding, ruminating, sleeping and resting. While the bucks and does A. axis significantly engaged in walking and feeding during fall, while autumn showed increased foraging and walking. In winter standing was enhanced, during spring they spent more time feeding, foraging, ruminating, and walking. Activities throughout the summer were mostly focused on sitting and resting. Furthermore, doe A. axis showed longer durations of sitting, ruminating, resting, sleeping and standing.